Education and income: methodological aspects and studies in Peru - Quiroz Vera, Eduardo Fernando (2008)
This text is a fragment of the work "Education and labor income in Peru", carried out by the authors with financing from the IECOS 2007 Competitive Fund. This section explains the Human Capital Theory according to which education is an investment to increase productive capacity. This theory makes it possible to use accessible empirical sources and calculate the real impact of education on income. The econometric estimates are made for the country as a whole and for three segments: area, sex and type of work. In a second section, there is an account of the studies carried out in Peru on education and the labor market.